2006
DOI: 10.1001/archinte.166.19.2138
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vancomycin Therapy for Methicillin-Resistant Staphylococcus aureus Infections

Abstract: High prevalence of clinical MRSA strains with elevated vancomycin MIC (2 microg/mL) requires aggressive empirical vancomycin dosing to achieve a trough greater than 15 microg/mL. Combination or alternative therapy should be considered for invasive infections caused by these strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
635
12
12

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 806 publications
(698 citation statements)
references
References 18 publications
35
635
12
12
Order By: Relevance
“…The data on nephrotoxicity at these higher troughs are limited. Previous studies that address the relationship between higher vancomycin troughs and nephrotoxicity suffer from small sample size 29,33 ; do not address reversibility of nephrotoxicity 9,26,[29][30][31]33 ; may not account for the temporal relationship between the development of nephrotoxicity and high trough levels, 9,28-31 or examine patient populations at relatively high 27 or low 30 risk for renal injury apart from receipt of vancomycin. A recent expert consensus statement identified these factors as limiting the strength of evidence for a direct causal relationship between elevated vancomycin troughs and nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data on nephrotoxicity at these higher troughs are limited. Previous studies that address the relationship between higher vancomycin troughs and nephrotoxicity suffer from small sample size 29,33 ; do not address reversibility of nephrotoxicity 9,26,[29][30][31]33 ; may not account for the temporal relationship between the development of nephrotoxicity and high trough levels, 9,28-31 or examine patient populations at relatively high 27 or low 30 risk for renal injury apart from receipt of vancomycin. A recent expert consensus statement identified these factors as limiting the strength of evidence for a direct causal relationship between elevated vancomycin troughs and nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…We initially decided to use maximum vancomycin trough !15 mg/L as the vancomycin exposure variable of interest to include in multivariable models, as we felt that (1) trough !15 mg/L is clinically relevant given current guidelines that recommend aiming for trough !15 mg/L for treatment of most invasive staphylococcal disease, 31 and (2) prior studies identified a single trough !15 mg/L as a possible risk factor for nephrotoxicity. 9,27,29,31 However, we also generated other multivariable models that included either maximum vancomycin trough !20 mg/L, mean vancomycin trough !15 mg/L, or mean vancomycin trough !20 mg/L, and models in which maximum and mean vancomycin troughs were treated as continuous variables. All variables were initially included in multivariable models; nonsignificant variables were removed from the models in a backwards stepwise fashion until likelihood ratio testing determined that removal of any variable was associated with likelihood ratio test P value <0.20 in comparing the full to reduced model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to tolerability and renal toxicity problems, a high treatment failure rate in severe infections has been reported for VAN, probably related to its poor tissue penetration in the lung, bone tissue, central nervous system (CNS), and inflammatory fluids (16)(17)(18)(19)(20). This requires use of higher doses, with the resultant increase in adverse events, one of the most significant of which is renal function impairment (21)(22)(23)(24)(25)(26). Despite these limitations, this glycopeptide continues to be widely used at Spanish ICUs.…”
Section: Introductionmentioning
confidence: 99%